2003
DOI: 10.1007/s00125-003-1268-4
|View full text |Cite
|
Sign up to set email alerts
|

Stable transplantation results of magnetically retracted islets: a novel method

Abstract: Aims/hypothesis. Large quantities of pure viable donor islets are necessary for clinical transplantation. At present, low yields and low viability of pancreatic islets after transplantation necessitate the use of multiple donors for a single recipient. In this study an improved method for obtaining large quantities of pure viable islets of Langerhans for transplantation was developed in the rat. Methods. Islets of Langerhans were isolated from Albino Oxford rats. The donor pancreata were perfused in situ with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Further improvements and adjustments in equipment design and implementation for specific applications (e.g., xeno-, allo-, or auto-transplants) may be required and may expand the benefits observed in this early study. It should also be noted that the islet labeling methods used for this study were established in literature [38, 48], in conjunction with QMS equipment and process improvements. Additional investigation is required to enhance infusion and labeling for human and porcine islets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further improvements and adjustments in equipment design and implementation for specific applications (e.g., xeno-, allo-, or auto-transplants) may be required and may expand the benefits observed in this early study. It should also be noted that the islet labeling methods used for this study were established in literature [38, 48], in conjunction with QMS equipment and process improvements. Additional investigation is required to enhance infusion and labeling for human and porcine islets.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic separation techniques have been used to purify islets by selective magnetic labeling of the endocrine [34, 36] or the exocrine tissue [37]. Islet yields and transplant outcomes in rats were improved when magnetic microparticles (MMPs) were preferentially entrapped within the tortuous islet microvasculature and purified using magnetic retraction [38]. Furthermore, developments in quadrupole magnetic separation (QMS) technology have shown promise for the large scale batch purification of porcine islets [39], with no observed detrimental effects on islet function due to magnetic forces or shear stresses [15, 40, 41].…”
Section: Introductionmentioning
confidence: 99%
“…They were anesthetized by a subcutaneous injection that contained a mixture of hypnorm and dormicum in PBS. The islets of Langerhans were isolated with the magnetic retraction technique (23). In brief, the descending aorta was perfused with a freshly sonicated 1.25% suspension of Fe 3 O 4 (Sigma-Aldrich, Zwijndrecht, the Netherlands) in PBS, after the thoracic aorta had been clamped.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, however, a method for magnetically labeling islets has been identified that eliminates the need for antibody labeling. In this new method, which has been adapted to the separation of other types of tissue, magnetic microparticles are infused into the vascular structure of the pancreas where they embolize in the islet capillaries [20]. By proper selection and sizing of microparticles, this ''labeling'' process can be made specific to the islets in the pancreas.…”
Section: Scaling Qmsmentioning
confidence: 99%